Equivalence of Parallel Combs to TDLs

It is easy to show that the TDL of Fig.2.19 is equivalent to a parallel combination of three feedforward comb filters, each as in Fig.2.23. To see this, we simply add the three comb-filter transfer functions of Eq.$ \,$(2.3) and equate coefficients:

\begin{eqnarray*}
H(z) &=& \left(1+g_1 z^{-M_1}\right) +
\left(1+g_2 z^{-M_2}\...
...\right) \\
&=& 3 + g_1 z^{-M_1} + g_2 z^{-M_2} + g_3 z^{-M_3}
\end{eqnarray*}

which implies

$\displaystyle b_0 = 3,\; b_{M_1} = g_1,\; b_{M_2} = g_2,\; b_{M_3} = g_3 .
$

We see that parallel comb filters require more delay memory ( $ M_1+M_2+M_3$ elements) than the corresponding TDL, which only requires $ \max(M_1,M_2,M_3)$ elements.


Next Section:
Equivalence of Series Combs to TDLs
Previous Section:
Filtered-Feedback Comb Filters